Monocyte‐Derived Macrophages Induce Alveolar Macrophages Death via TNF‐α in Acute Lung Injury - Junjie Xiao; Fei Hou; Huan Wang; Ruixuan Wang; Ying Liu; Xiayan Wu; Lixin Xie (Immunity, Inflammation and Disease)
ABSTRACT Introduction Acute lung injury (ALI) and its subsequent progression to acute respiratory distress syndrome (ARDS) are severe respiratory conditions. They are marked by rapid lung function deterioration and extensive pulmonary inflammation, often resulting in critical patient outcomes. Alveolar macrophages (AMs) and monocyte‐derived macrophages (MDMs) are two distinct subsets of lung macrophages present in the alveoli during ALI. Both are critical mediators of pulmonary inflammation. Our study examined the interplay between AMs and MDMs in the inflammatory environment of ALI/ARDS. Methods Mice were treated with lipopolysaccharide (LPS) to establish ALI models. The lung tissues of mice were subjected to hematoxylin‐eosin staining to observe the degree of tissue damage. In vivo, CCR2‐deficient mice or depleting peripheral blood mononuclear cells by clodronate liposomes were used to reduce MDMs recruitment. The bronchoalveolar lavage fluid (BALF) supernatants were used for cytokine and total protein analyses. AMs and MDMs in the BALF were analyzed by flow cytometry. The levels of AMs death were determined through propidium iodide staining and measured by flow cytometry. In vitro, primary AMs were exposed to MDM‐conditioned medium or TNF‐α, and their death levels were assessed under a fluorescence microscope with propidium iodide staining. Results AMs significantly decrease in number and undergo extensive cell death during ALI. The reduced MDMs recruitment can increase the number of AMs, reduce AMs death, and alleviate lung injury. In vitro, MDM‐conditioned medium can induce AMs death and TNF‐α is one of the major secretions. It indicates that TNF‐α stimulation in vitro promotes AMs death. In vivo, MDMs are identified as the primary cells secreting TNF‐α. Additionally, the treatment with TNF‐α antagonists can reduce AMs death and the severity of lung injury. Conclusion Our study demonstrates that MDMs contribute to AMs death during ALI through TNF‐α. Targeting TNF‐α may offer a therapeutic strategy to mitigate AMs death and lung injury in ALI/ARDS.